2019
DOI: 10.1208/s12249-019-1535-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Aerosolization Using Computational Fluid Dynamics in a Pediatric Air-Jet Dry Powder Inhaler

Abstract: The objective of this study was to optimize the performance of a high efficiency pediatric inhaler, referred to as the pediatric air-jet DPI, using computational fluid dynamics (CFD) simulations with supporting experimental analysis of aerosol formation. The pediatric air-jet DPI forms an internal flow pathway consisting of an inlet jet of high-speed air, capsule chamber containing a powder formulation, and outlet orifice. Instead of simulating full breakup of the powder bed to an aerosol in this complex flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The air-jet DPI consists of a small diameter inlet passage, aerosolisation chamber and small diameter exit passage and gas at positive pressure passes from it and forms a turbulent jet within the aerosolisation chamber. Using CFD, they optimised the performance of the air-jet DPI [ 77 , 89 ].…”
Section: Application Of Computation Modelling For Emerging Dpi Desmentioning
confidence: 99%
See 1 more Smart Citation
“…The air-jet DPI consists of a small diameter inlet passage, aerosolisation chamber and small diameter exit passage and gas at positive pressure passes from it and forms a turbulent jet within the aerosolisation chamber. Using CFD, they optimised the performance of the air-jet DPI [ 77 , 89 ].…”
Section: Application Of Computation Modelling For Emerging Dpi Desmentioning
confidence: 99%
“…This could potentially affect the overall dispersion performance of the DPI. Several recent studies [ 77 , 89 , 97 ] have suggested that the particle dispersion in the capsule was strongly correlated with the parameters which were used to describe the turbulence of the flow. This can be further explored for the development of a low-computational-cost modelling approach considering the effect of particle discharging from the capsule.…”
Section: Challenges and Future Workmentioning
confidence: 99%
“…However, intrinsic differences between various in vitro, and in vitro and in silico methods complicate direct comparison between experimental and simulated data. A number of studies in parallel assessed the results of CFD simulations and in vitro experimental results (usually including a single in vitro method such as MSLI, NGI or ACI) [35][36][37][38][39]41,[44][45][46][47][48][49][50][51][52][53]. Overall, some correlation between in vitro and in silico CFD results has been detected [48][49][50][51][52][53], but there is a need for additional comparative assessment of CFD tools in relation to the in vitro methods to evaluate the applicability of CFD in the research and development of various DPI formulations.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies in parallel assessed the results of CFD simulations and in vitro experimental results (usually including a single in vitro method such as MSLI, NGI or ACI) [35][36][37][38][39]41,[44][45][46][47][48][49][50][51][52][53]. Overall, some correlation between in vitro and in silico CFD results has been detected [48][49][50][51][52][53], but there is a need for additional comparative assessment of CFD tools in relation to the in vitro methods to evaluate the applicability of CFD in the research and development of various DPI formulations. A recent review study of Zheng et al (2021) also concluded that more direct comparison between the simulated and experimental results is necessary to improve the prediction accuracy of in silico tools [54].…”
Section: Introductionmentioning
confidence: 99%